‘Sales’ on Retention of Title terms: is the English law analysis broken? - Gullifer, L (Sweet & Maxwell, 2017)
Hard cases make bad law. The history of the Bunkers litigation in the English courts demonstrates, as is often the case, that the history and context of litigation can have a strong and decisive effect on both the result and the legal reasoning leading to that result. This article argues that, while the decision of the Supreme Court in the Bunkers case was understandable given its context and background, it, together with the decision of the Court of Appeal in Caterpillar v Holt, has led to such uncertainty surrounding the use of retention of title (‘ROT’) clauses in inventory financing, that it is time for a reanalysis of the legal position. This article sets out suggested options for that reanalysis, some more radical than others.